Complicated Posterior Sternoclavicular Joint Dislocation with Aortic Arch Impingement - Domagoj Lemac; Ivo Dumić-Čule; Ante Legac; Tomislav Čengić; Igor Nikolić; Igor Čikara; Boris Brkljačić; Gordana Ivanac (Acta Clinica Croatica, 2024)
Posterior sternoclavicular dislocation accompanied by clavicular end fracture is an extremely rare injury according to the available literature. We present a case of a young male with this injury, resulting from a vehicle accident, and additionally complicated by a clavicular bone fragment in the proximity of the aortic arch. An initial X-ray showed no signs of bone trauma, which was, however, revealed on a CT scan. Stable fixation of the fragment and sternoclavicular joint was achieved utilizing a plate and screws. The osteosynthetic material was removed after eight weeks due to the plate breaking. There were no complications in the 5-year follow-up period, and a full range of motion was accomplished. We aimed to emphasize the importance of early diagnosis and appropriate surgical management of complicated posterior sternoclavicular dislocations to avoid life-threatening events.